A low carbon balance triggers Microvine inflorescence abscission at high temperatures - Luchaire, Nathalie; Torregrosa, Laurent Jean-Marie; Gibon, Yves; Rienth, Markus; Romieu, Charles; Ageorges, Agnès; Turc, Olivier; Muller, Bertrand; Pellegrino, Anne (Frontiers in Horticulture, 2023)
Global warming is a major threat for yield sustainability of most crops, including grapevine. Whether grapevine fruitfulness is impaired by an imbalance between carbon supply and demand caused by high temperature was addressed in the present study. Five experiments were conducted on Microvine, a natural mutant of grapevine insensitive to gibberellins, with dwarf stature and continuous flowering along vegetative axes. This property was used to infer temporal patterns of inflorescence development from their spatial distribution at harvest. Two sets of plants characterized by low or high initial shoot vigor were grown under contrasted day/night temperatures: 22/12°C vs 30/20°C. The rate of leaf development of the main shoot was stable, regardless of the initial vigor and temperature treatments. In contrast, warm temperatures delayed the timing of flowering for low vigor plants or of onset of ripening for high vigor plants. Fruitfulness was impaired by high temperature, due to the abscission of young inflorescences (before the flowering stage). From a careful spatio-temporal analysis of cluster abscission, we conclude that inflorescence drop under elevated temperatures was triggered by the increase of plant carbon demand due to the oldest clusters starting to unload sugars. Elevated temperatures may have also lowered the carbohydrate supply in the zone of inflorescence abscission, due to the higher leaf respiration, while all organ growth demand was maintained. Interestingly, inflorescence abscission occurred earlier when whole plant vigor was low, and was followed by a recovery period, in spite of a lower non-structural sugar status as compared to high vigor plants. Taken together, our results suggest that inflorescence abscission is linked to the variations of carbon pool induced by temperature contrasts, and not to its absolute value. Our study therefore provides new hypotheses about the impacts of warm temperatures on the regulation of temperature-induced reproductive failure in grapevine.